Peningkatan Kadar Glukosa Darah Terhadap Infeksi Tuberculosis Penderita Diabetes Militus Puskesmas Ngasem, Kediri - Damono, Ravega Surya Adam; Enny Willianti; Emillia Devi Dwi Ratnasari (Calvaria Medical Journal, 2026)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a major global public health problem. In Indonesia, 397,377 TB cases were detected in 2021, while the treatment success rate has not yet reached the expected target. Objective: This study aimed to analyze the association between blood glucose levels and TB infection among patients with diabetes mellitus at Ngasem Primary Health Center, Kediri Regency. Methods: This observational study employed an analytical approach. The study population consisted of 131 patients with diabetes mellitus, of whom 99 respondents were selected using purposive sampling. The independent variable was blood glucose level, while the dependent variable was TB infection. Results: Data were analyzed using Fisher’s Exact Test. The findings showed that most respondents had uncontrolled blood glucose levels (53.5%), and the majority were not infected with TB (84.8%). Statistical analysis revealed a significant association between blood glucose levels and TB infection among patients with diabetes mellitus (p = 0.001). Conclusion: These findings indicate the importance of maintaining optimal blood glucose control to reduce the risk of TB infection among patients with diabetes mellitus.